Development of a functional plant protein blend : a thesis presented in partial fulfillment of the requirements for the degree of Master of Food Technology, Massey University, Palmerston North, New Zealand. EMBARGOED until 9th October 2027 - Kannan, Aarthy (Massey University, 2025)
Advanced plant-based protein systems are being developed in response to the growing demand for sustainable, nutritionally adequate substitutes for animal-derived proteins. To achieve a balanced essential amino acid profile while preserving desired functional qualities, this study investigated the composition of a multi-source plant protein blend. Certain plant proteins were mixed in ratios intended to enhance one another's nutritional and technical qualities. Solubility, structural characterization, and rheological analysis were used to evaluate the functional performance, and the nutritional quality was compared to global reference patterns. The findings showed that although the solubility and structural stability of individual plant proteins varied, specific processing methods increased dispersibility, changed secondary structures, and improved flow characteristics in concentrated suspensions. These results show that plant-based protein systems with enhanced nutritional value can be produced through careful blending and processing.
Embargoed until 9th October 2027.
Keywords: 300607 Food technology